Unlocking Finance through Social Networks : Attracting investment for the high-tech Swedish startups in Luleå, Sweden - Wijewarna Arachchi, Thilini Nimesha (Luleå tekniska universitet, Institutionen för ekonomi, teknik, konst och samhälle, 2022)
The importance of entrepreneurship for economic growth and development is a well-known factor in the world. In which high technology startup firms are playing an important role in introducing innovative and advanced technologies. However, due to inherent difficulties in nature, they face major challenges such as acquiring sufficient investments. Especially for high-tech startups founded and located in non-main cities facing the issue compared to main cities. As a result, the firms tend to move out from the non-main city or region to main cities or abroad seeking investments. Such trends directly affect negatively in the regional economic development goals and plans. Therefore, the purpose of this study is to address such tendencies by focusing on the Luleå city in Northern Sweden, investigating the ways of attracting local and global investors through social networks, for high technology startup firms in non-main cities, and identify the possibility of use digitalization to support to overcome the geographical distances to retain them within the region. This empirical study is exploratory in nature and used qualitative methodology with an inductive research approach. In order to collect the data, the research performed expert interviews by interviewing top management in high-tech startups, incubators, and science parks in two cities (i.e. Luleå and Stockholm) from two regions in Sweden. To perform in-depth semi-structured interviews, an interview guide was used and analyzed the gathered data using the pattern matching method. As the findings of this study, selected social networks for this study; multilevel and multiplex networks are modified, and presented in the context of high-tech startup ecosystems to attract and expand the investor networks out of geographical boundaries. The use of such networks is based on the amount of investment required, purpose, and aim of the high-tech startup firm. A six steps model has been introduced to Incubators to assist their high-tech startups through investor attractions. ...